Idiopathic calcium nephrolithiasis. 2. Differences between hypercalciuric and normocalciuric persons with recurrent kidney stone formation and persons without such a history. - Wilson, D. R. (1979)
Normocalciuric and hypercalciuric patients with idiopathic recurrent calcium nephrolithiasis were compared with healthy individuals without such a history to examine the factors that predispose normocalciuric patients to stone formation. The urine calcium excretion rate was higher in the normocalciuric patients than in the control subjects (227 v. 183 mg/24 h; P less than 0.01), but the urine calcium concentration was not significantly different. The urine magnesium and citrate excretion rates and concentrations were lower in the normocalciuric patients than in the control subjects (P less than 0.001), while the urine uric acid and oxalate excretion rates and concentrations and the urine saturation with brushite (CaHPO4-2H2O) were not significantly different. These results suggest the importance of slight increases in the urine calcium excretion rate together with decreased urine magnesium and citrate excretion rates in normocalciuric persons with recurrent calcium stone formation. The urine of the hypercalciuric patients was more highly saturated with brushite than the urine of the normocalciuric patients and the control subjects, and the excretion rates of uric acid and oxalate were increased in the hypercalciuric patients. The hypercalciuric patients had a higher urine creatinine excretion rate than the normocalciuric patients and a higher daily urine volume than the control subjects, which suggests that differences in lean body mass or fluid and food intake, or both, may be important determinants of these differences in crystalloid excretion. As in the normocalciuric patients, the urine citrate excretion rate and concentration were decreased in the hypercalciuric patients compared with the control subjects.